Preventing Malnutrition through Adequate Management of Gastrointestinal Dysmotility in Systemic Sclerosis Patients: A Literature Review - Layadi, Eka Benhardi; Pribadi, Rabbinu Rangga; Teressa, Maria; Suharja, Felicia; Ichsan, Oemar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Gastrointestinal dysmotility in systemic sclerosis occurs as the end result of extensive fibrosis of the gastrointestinal tract. The entire length of the tract from the esophagus to the anorectum could be affected, exerting various gastrointestinal symptoms. Clinical manifestations attributed to gastrointestinal dysmotility are associated with significant distress and an increased risk of nutritional impairment, reducing the the quality of life of systemic sclerosis patients. One of the most commonly overlooked gastrointestinal implications in systemic sclerosis is malnutrition. Once malnutrition ensues in the course of systemic sclerosis, the detrimental effects attributed to nutritional decline are difficult to reverse and pose an increased risk of mortality. Adequate management through timely diagnosis of gastrointestinal dysmotility and utilization of malnutrition screening tools for systemic sclerosis patients could prevent the progression to malnutrition and its negative impacts.